Risks related to the use of anabolic steroids for aesthetic purposes (Research, Society and Development, 2022)
The study addresses the aspects surrounding Anabolic Androgenic Steroids (AAS) medications to improve appearance and performance, as these are most often used by men to improve appearance, increase muscle mass or athletic performance, highlight- the effects of drugs such as Deposteron, Sustanon and Deca-Durabolin will be seen. To analyze the health risks of the use of anabolic steroids used for aesthetic purposes. To achieve the objectives, the deductive method will be used, as a methodology the bibliographic research, with exploratory purposes having as source of data articles, theses and dissertations from online databases PUBMED, MEDLINE, Scielo and Virtual Health Library (BVS), published between 2014 to 2022. Initial studies indicate that supraphysiological and polypharmacological doses of anabolic androgenic steroids induce dose-dependent physiological and psychological side effects. It is concluded that the consequences of prolonged use of AAS, as well as its role in the genesis of certain types of cancer, remain poorly understood, but many physiological and psychological side effects are described in the literature. Thus, specialized monitoring of the use of these drugs is necessary at the risk of these factors becoming a public health problem.